Orientation-specific amorphization and intercalated recrystallization at ion-irradiated SrTiO3/MgO interfaces. Issue 16 (27th August 2014) - Aguiar, Jeffery A.; Zhuo, Mujin; Bi, Zhenxing; Fu, Engang; Wang, Yongqiang; Dholabhai, Pratik P.; Misra, Amit; Jia, Quanxi; Uberuaga, Blas P.
Abstract